Environmental Factors Affecting Human Health - Uher, Ivan (IntechOpen, 2020)
Raising the average human lifespan by a decade or more will change our world. The future is not about whether this will happen; it is about what we should do when it happens. Even the most pessimistic assertions about the future of our environment are underestimating the extent of the problem. There is simply no model in which more years of life does not equate to more people and in which that does not lead to more crowding, environmental degradation, more consumption, and more waste. Hence, as we prolong life, these environmental crises will be further exacerbated. With current diets and production practices, feeding 7,6 billion people is degrading terrestrial and aquatic ecosystems, depleting water resources, and driving climate changes. The challenges of today are not just population, and it's not just consumption, it is waste also. Thanks to things such as cars, planes, big homes, deforestation and so forth, the annual carbon dioxide emissions of an average are three times as high as it should be. It is likely that this signals that the current level of dividends is unsustainable, hence, we use and return little of value to our natural world. In our book, we address the questions related to environmental health challenges that include contamination of air, water, and soil, and car transportation. In order to better understand natural, industrial, and social-environmental hazards, we have to think of them in a broader context (i.e., physical, chemical, biological, and cultural). We hope that the presented publication gives the reader a broader perspective on the issues related to environmental health challenges in contemporary society in the coming years.